Wilson Disease: Why Early Diagnosis Matters and How to Improve Screening - Starzyk, Agnieszka; Charzewski, Piotr (Quality in Sport, 2025)
Wilson disease is a genetic disorder of copper metabolism caused by mutations in the ATP7B gene, leading to copper accumulation in the liver, brain, and other organs. This results in hepatic, neurological, and psychiatric symptoms, including cirrhosis, movement disorders, cognitive impairment, and mood disturbances. Diagnosis relies on biochemical tests (serum ceruloplasmin, urinary copper excretion, hepatic copper quantification), genetic testing, and neuroimaging. Lifelong copper management is the mainstay of treatment, with chelating agents (D-penicillamine, trientine) and zinc therapy used to control copper levels. Liver transplantation remains the only curative option for patients with severe liver failure. However, treatment adherence, side effects, and the lack of effective therapies for neurological symptoms remain challenges. Recent research focuses on gene therapy to restore ATP7B function, improved copper chelators with fewer side effects, and microbiome-targeted therapies. Despite these advancements, early detection, personalized treatment approaches, and long-term disease monitoring remain critical to improving patient outcomes and quality of life.